1990
DOI: 10.1139/b90-016
|View full text |Cite
|
Sign up to set email alerts
|

Litter decomposition under snow cover in a balsam fir forest

Abstract: In a subalpine balsam fir forest in Quebec, Canada, mass losses, respiration rates, and nitrogen and sulphur dynamics were measured on fir needles, birch leaves, lichens (mixed species), and small twigs decomposing under deep (> 1.5 m) winter snow for 6 months. Mass losses ranged from <6% (twigs) to 70% (lichens) and relative decomposition rates of needles and leaves were reversed from those expected at higher temperatures. Isolation of fir needles from direct contact with the snow did not affect decay r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 22 publications
2
34
0
Order By: Relevance
“…Melting snow is a very likely source of N and P, and birch leaves and some fir needles could assimilate N and P from the environment (Taylor and Jones 1990). N or P content increases because microbes immobilize N and P after plant senescence in the autumn, and, thus, the released N and P are retained throughout the winter (Lipson et al 1999;Uchida et al 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Melting snow is a very likely source of N and P, and birch leaves and some fir needles could assimilate N and P from the environment (Taylor and Jones 1990). N or P content increases because microbes immobilize N and P after plant senescence in the autumn, and, thus, the released N and P are retained throughout the winter (Lipson et al 1999;Uchida et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The litter traits of plant species are important factors that control the decomposition rate of organic matter in ecosystems (Cornelissen 1996;Cornwell et al 2008). For example, needles, hardwood leaves, grass, and forbs showed different mass loss rates, 10.0, 15.6, 21.0, and 39.0 %, respectively, under snow cover in a balsam fir (A. balsamea) forest over a 6-month snow-covered season (Taylor and Jones 1990). Moreover, the decomposition rate of different plant types is generally in the order of forbs [ graminoids [ deciduous shrubs [ evergreen shrubs (Cornelissen 1996;Cornelissen et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in resources probably represents the release of inorganic nutrients in free water in late winter and during spring thaw that had accumulated over winter, as a result of fragmentation of plant litter, cell lysis, leaching of nutrients from tissues and mineralization (Hobbie and Chapin, 1996). Taylor and Jones (1990) concluded that decomposition over the winter usually led to a loss of between 40% and 60% of the litter mass, based on the results from 17 studies. In addition to inorganic nutrients, pools of soluble organic C and N also rose in early April and much of this organic C and N was probably derived from the lysis of microbial necromass that had remained in a frozen state over the winter.…”
Section: Freeze-thaw Cycles and Nutrient Availabilitymentioning
confidence: 99%
“…Furthermore, microbial biomass and the activities of several soil enzymes were even found to peak in late winter in alpine soils (Lipson et al 1999(Lipson et al , 2002. Furthermore, significant plant litter decomposition was found in winter in seasonally snow-covered ecosystems (Taylor and Jones 1990, Hobbie and Chapin 1996, Schmidt and Lipson 2004.…”
Section: Introductionmentioning
confidence: 99%